2019
DOI: 10.1002/glia.23614
|View full text |Cite
|
Sign up to set email alerts
|

Grey matter myelination

Abstract: There is now increasing evidence that myelin is not only generated early in development, but also during adulthood possibly contributing to lifelong plasticity of the brain. In particular, human cortical areas responsible for the highest cognitive functions seem to require decades until they have reached their maximal amount of myelination. Currently, we know very little about the mechanisms and the functions of grey matter myelination. In this emerging field key questions await to be addressed: How long does … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 84 publications
3
57
0
Order By: Relevance
“…Moreover, we found that, while the lesions showed uniform negative (Timmler and Simons, 2019). This finding is concordant with the few QSM studies that have evaluated whether iron is co-localised with myelin in deep cortical layers in healthy subjects (Deistung et al, 2013;Stüber et al, 2014).…”
Section: Measurements Of Across Cortical Depth In Groups With Well-losupporting
confidence: 91%
“…Moreover, we found that, while the lesions showed uniform negative (Timmler and Simons, 2019). This finding is concordant with the few QSM studies that have evaluated whether iron is co-localised with myelin in deep cortical layers in healthy subjects (Deistung et al, 2013;Stüber et al, 2014).…”
Section: Measurements Of Across Cortical Depth In Groups With Well-losupporting
confidence: 91%
“…In humans, myelination and white matter development occur at a high rate in the first years of childhood [7], continue at a slightly slower rate during adolescence, and enter another dynamic phase in cortical areas during young adulthood [8], a vulnerable period of brain development that coincides with the average age of onset of SZ [9]. In some cortical areas, myelination contributes to lifelong brain plasticity, an adaptive process to "learning," and only reaches its maximum level after decades [10].…”
Section: Introductionmentioning
confidence: 99%
“…AD is pathologically defined by β‐amyloid (Aβ) neuritic plaques, tau neurofibrillary tangles, and is associated with neuronal, axonal, and synaptic degeneration (Braak & Braak, ; Selkoe, ). Myelin, the insulating sheath surrounding neuronal axons, is vulnerable to AD pathology while it is essential for efficient neuronal communication by fine‐tuning conduction speed and synchronization, thereby affecting brain connectivity (Nave & Werner, ; Timmler & Simons, ). A failure in cerebral connectivity has been shown to interfere with healthy cognitive functioning (Fornito, Zalesky, & Breakspear, ; Pievani, Filippini, Van Den Heuvel, Cappa, & Frisoni, ).…”
Section: Introductionmentioning
confidence: 99%